Polystyrene Microplastics in Aquatic Rearing Systems: Impacts on Growth Performance and Histomorphometry of the Giant Freshwater Prawn (Macrobrachium rosenbergii) - Nurul Suwartiningsih; Luqman Hakim Yusuf; Rani Swita; Rani Marsela; Dian Eka Wijayanti; Aulia Fayzha Aszhara; Iga Novianti (Jurnal Penelitian Pendidikan IPA, 2026)
Polystyrene (PS) microplastics are widely detected in aquatic environments, particularly in freshwater ecosystems, and may pose ecological risks to aquatic organisms. However, information on how PS microplastics affect the giant freshwater prawn, an economically important freshwater aquaculture species, remains limited, particularly at the tissue level. This study therefore investigated the effects of PS microplastics in rearing media on microplastic accumulation, growth performance, and histomorphometry of the giant freshwater prawn. Following a three-day acclimation period, prawns were exposed to four concentrations of PS microplastics (0, 1, 10, and 100 mg/L) for 14 days. Growth parameters (length and weight), microplastic abundance in organs (gills, intestine, and muscle), and histomorphometry of the gills, intestine, and muscle were evaluated using hematoxylin–eosin staining. Data were analyzed using analysis of variance or Kruskal–Wallis tests followed by Duncan’s test and regression analysis. The results showed that microplastic abundance in the rearing media significantly increased microplastic accumulation in the gills and muscle (p < 0.05), but not in the intestine (p > 0.05). Exposure to PS microplastics did not significantly affect growth performance or gill lamella length (p > 0.05). However, significant alterations were observed on intestinal histological parameters and muscle myofiber structure (p < 0.05). These findings demonstrate that PS microplastics can induce tissue-level alterations in M. rosenbergii despite the absence of short-term growth effects.